2017
DOI: 10.1016/j.bbr.2017.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Drunk bugs: Chronic vapour alcohol exposure induces marked changes in the gut microbiome in mice

Abstract: The gut microbiota includes a community of bacteria that and play an integral part in host health and biological processes. Pronounced and repeated findings have linked gut microbiome to stress, anxiety, and depression. Currently, however, there remains only a limited set of studies focusing on microbiota change in substance abuse, including alcohol use disorder. To date, no studies have investigated the impact of vapour alcohol administration on the gut microbiome. For research on gut microbiota and addiction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…2. Preclinical Literature-Consistent with the clinical literature, preclinical studies in rodent models of alcohol abuse also indicate that alcohol induces gut dysbiosis, though the exact microbial communities that are altered varies from study to study-likely due to differences in alcohol administration regimen as well as concomitant liver disease (Mutlu et al 2009;Yan et al 2011;Bull-Otterson et al 2013;Zhang et al 2015;Peterson et al 2017;Samuelson et al 2017;Xiao et al 2018;Xu et al 2018;Zallar et al 2019). For instance, one group found that chronic alcohol feeding in mice resulted in decreased relative abundance of both Bacteroidetes and Firmicutes as well as an increased relative abundance of Proteobacteria and Actinobacteria in stool samples (Bull-Otterson et al 2013).…”
Section: The Gut Microbiome In Addictionmentioning
confidence: 70%
See 1 more Smart Citation
“…2. Preclinical Literature-Consistent with the clinical literature, preclinical studies in rodent models of alcohol abuse also indicate that alcohol induces gut dysbiosis, though the exact microbial communities that are altered varies from study to study-likely due to differences in alcohol administration regimen as well as concomitant liver disease (Mutlu et al 2009;Yan et al 2011;Bull-Otterson et al 2013;Zhang et al 2015;Peterson et al 2017;Samuelson et al 2017;Xiao et al 2018;Xu et al 2018;Zallar et al 2019). For instance, one group found that chronic alcohol feeding in mice resulted in decreased relative abundance of both Bacteroidetes and Firmicutes as well as an increased relative abundance of Proteobacteria and Actinobacteria in stool samples (Bull-Otterson et al 2013).…”
Section: The Gut Microbiome In Addictionmentioning
confidence: 70%
“…To control for confounding effects of inconsistent alcohol dose resulting of variable food consumption amongst subjects, Peterson et al (2017) instead investigated the effects of chronic intermittent vaporized alcohol (CIE) exposure on the composition of the gut microbiome in C57BL/6J mice. They found an overall decrease in alpha diversity in the CIE mice.…”
Section: The Gut Microbiome In Addictionmentioning
confidence: 99%
“…Caecum was collected following three months of abstinence under aseptic conditions and snap-frozen on dry ice. Protocols for microbiome sequencing were used as previously described (Peterson et al, 2017…”
Section: Ceacal Microbiome Collection and Sequencingmentioning
confidence: 99%
“…Although the source of this neuroinflammation is not yet understood, growing evidence suggests that alterations in microbiota composition may contribute to neuroimmune processes and peripheral inflammation (de Timary et al, 2015;Gorky and Schwaber, 2016;Rea et al, 2016). Changes in the gut microbiome have been reported in both human alcoholic individuals and murine models of chronic alcohol exposure, with increased intestinal permeability (causing endotoxin to escape into the circulation and impact the host), increased abundance of pro-inflammatory gut microbes, like Proteobacteria species, and decreased abundance of normal commensal bacteria like Bacteroidetes (Bull-Otterson et al, 2013;Leclercq et al, 2017;Mutlu et al, 2012;Peterson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although gut microbial alterations related to chronic alcohol use are supported, the mechanism of action is still unclear (Vassallo et al, 2015). A recent preclinical study evaluating the effect of vaporized ethanol administration in mice demonstrated elevated alpha diversity, significantly increased Alistipes genus, and significantly diminished genra Clostridium IV and XIVb, Dorea, and Coprococcus between mice exposed to ethanol vapor and controls (Peterson et al, 2017). Additionally, current understandings of the effect of drugs abuse on the gut microbiota are sparse, although differences have been demonstrated between the commensal gut microbiota of cocaine users and control subjects (Volpe et al, 2014).…”
Section: Gut Microbiota Dysbiosis and Alcohol And Substance Use Disomentioning
confidence: 99%